Differential temporal coding of the vibratory sense in the hand and foot in man - Tobimatsu, Shozo; Zhang, You Min; Suga, Rie; Kato, Motohiro (Clinical Neurophysiology, 2000)
Objective: We studied the difference in the temporal tuning function of the vibratory senses between the hand and foot in man by using steady-state somatosensory evoked potentials (S-SEPs) to vibratory stimulation. Methods: Vibratory stimuli were applied to the palm and sole, and the S-SEPs were then recorded in 8 normal subjects. A total of 200 responses were recorded from 4 electrodes including the ipsi-and contralateral somatosensory areas of the hand and foot. The amplitude of the first harmonic component (1F) was obtained by a Fourier analysis. The effect of modulation frequency (17–30 Hz) on the 1F at a stimulus intensity of 0.05 N was studied. Results: The amplitudes of the S-SEPs were the greatest in the contralateral hand and foot areas. The mean 1F amplitudes of the palm S-SEPs as a function of the modulation frequency showed a narrow tuning curve with a peak near 21 Hz while those of the sole demonstrated a broad tuning curve. Conclusion: Our results suggest the differential temporal coding of the vibratory sense in the hand and foot areas of the somatosensory cortex in man. This is probably caused by the different characteristics in the receptors situated in the hand and foot.